Evaluasi Efektivitas Pembelajaran Daring terhadap Prestasi Belajar Siswa Sekolah Dasar di Indonesia - Sugiarti, Iis (Diniyah: Jurnal Pendidikan Dasar, 2023)
Online learning has become a primary solution to sustain education during the pandemic; however, its effectiveness on student achievement remains debatable. This study aims to describe the implementation of online learning at MIN 1 Kendari and evaluate its effectiveness in improving students' academic performance. The research employed a descriptive quantitative method using a survey technique, involving 34 fourth-grade students as the sample, with questionnaires and documentation as data collection instruments. The results revealed that most students struggled to maintain focus, experienced physical and psychological complaints, and preferred face-to-face learning methods. Statistical analysis indicated that online learning had no significant impact on improving students' academic achievement. Limited access to technology, lack of interactive media variety, and psychosocial factors were identified as key causes of low effectiveness. These findings highlight the urgent need for innovation through blended learning approaches and strengthening both technical and emotional support to enhance the quality of education at the madrasah ibtidaiyah level.Keywords: Online learning, learning effectiveness, academic achievement, madrasah ibtidaiyah, blended learning